Consensus and Uncertainty in Economic Prediction - Zarnowitz, Victor; Lambros, Louis A. (Journal of Political Economy, 1987)
The authors define "consensus" as the degree of agreement among point predictions aimed at the same target by different individuals and " "uncertainty" as the diffuseness of the corresponding probability distributions. This distinction is made operational with the aid of the NBERAASA survey data on matched point and probabilistic forecasts of inflation and the rate of change in gross national product. The means of the two sets of forecasts agree closely. Standard deviations of point forecasts tend to understate uncertainty as measured by standard deviations of the predictive probability distributions. However, these measures of consensus and uncertainty are on the whole positively correlated. Copyright 1987 by University of Chicago Press.